A computerized tool to assess reading skills of students with motor impairment. (March 2020) - Bissaco, Marcia Aparecida Silva; Frere, Annie France; Bissaco, Luiz Fernando; Manrique, Ana Lucia; Dirani, Ely; Rugerro, Niube; Amate, Flavio Cezar
Highlights: The same computer tool can perform assessments of students with and without special needs reducing inequalities and favouring school inclusion. The assessment of students can be performed without the dependence of a teacher and therefore done without subjectivity. The assessment does not require complex or precise movements or sophisticated peripherals. No mouse movements or double clicks are needed. The assessment of reading skills of students with motor impairment is important to develop appropriate teaching strategies and approaches. Abstract: Conventional tests for assessing the early reading skills of preschool children on school entry are not accessible to students with motor limitations of upper limbs. This paper presents a game-like computerized test featuring an appealing scenario that is accessible to these students. It was developed on a platform that creates 2D vector graphics and contains three phases of interactive content accessible through an adapted peripheral. A conventional card-based test was also used to validate the effectiveness of the computerized test. Both tests were performed by thirty-three preschool children without mobility impairment all aged between four years and six months and six years and two months ( x ¯  = 5, 33; σ = 0, 44). The Wilcoxon signed-rank test was used to compare the nonparametric data from the computerized test with the card-based test in the first and second phase, yielding results of p  = 0.11 and p  = 0.21, respectively. The Student's t-test was conducted to compare the parametric data of the third phase of the computerized test with the data from the third phase of the card-based test yielded results of p  = 0.07.Three gaming experts considered the computerized test to be fun and engaging, and three teachers concluded that the computerized test meets educational goals. Additionally, seven volunteers with moderate mobility impairment (group T), aged between eight and seventeen years old ( x ¯ =11.8; σ = 3.5), accompanied by two physical therapists, took the computerized test using the adapted peripheral device and performed the required tasks without difficulty and without showing signs of fatigue. Based on the results obtained it can be concluded that the computerized test may enable educators to include students with mobility difficulties in literacy assessments and to design teaching strategies that are appropriate given their levels of knowledge.